GAMBARAN PENGETAHUAN DAN MOTIVASI IBU TENTANG PEMBERIAN IMUNISASI DPT LANJUTAN (BOOSTER) DI PUSKESMAS SIMPANG IV SIPIN KOTA JAMBI - Risya Ramadhanti Harahap; Tuhu Perwitasari; Aryani Puspasari (Universitas Baiturrahim, 2019)
According to World Health Organization (WHO), there are 1.5 million children die every year from diseases that can actually be prevented by immunization. From 194 WHO member countries, 65 of them have diphtheria, pertussis and tetanus (DPT) immunization coverage below the global target of 90%. The high incidence of DPT in Indonesia makes the government try to do advanced DPT (Booster) immunization, because DPT immunization (Booster) is important in an effort to maintain high levels of immunity so that it can provide optimal protection. This study aimed to determine the description of knowledge and mother’s motivation that have toddler about giving advanced DPT immunization (Booster) at the public health center Simpang IV Sipin Jambi city year 2019. This is a descriptive research. It was conducted on August 10th – 16th 2019 at the public health center Simpang IV Sipin. Populations were all of mothers who have toddlers period January – May 2019 as many as 1737 mothers. Samples were 79 respondents by using Accidental Sampling technique. The instruments used a questionnaire. Data analyzed as univariate. From 79 respondents, most them have lack of knowledge as many as 44.35 respondents. 50.6% respondents have high motivation. Most of toddlers did not get advanced DPT immunization (Booster) as many as 82.3%. This study can be concluded that most of respondents have lack of knowledge, high motivation and most of toddlers did not get advanced DPT immunization (Booster). The health personals should provide counseling to toddler’s mothers that can be done when visiting to toddlers Posyandu and also can provide information on patients visiting the public health center so that mothers can do advanced immunizations (Booster).